PENGARUH RASIO KEUANGAN TERHADAP HARGA SAHAM - Istiyana Muriyastuti, 10.05.52.0208; Wardjono, Wardjono (Students Journal of Accounting and Banking, 2012)
Thi s research aim to determine and analyze the effect of CAR (Capital Adequacy Ratio), KAP (Earning Assets), BOPOÂ  (Operating Expenses to Operating Income) and LDR (Loan toÂ  Deposit Ratio) to stock price. Population to be studied were the banking companies listed in Indonesia Stock Exchange in 2007-2010. With a purposive sample method, the samples used were 22 banking companies. Analysis of the data used in this research is the classical assumption perfomed, multiple regression analysis, the strength of the model and performed, hypotheses performed.The results of this research is the CAR (Capital Adequacy Ratio) has a negative effect and no significant to stock price. Therefore, the first hypothesis (H1) which states that the CAR (Capital Adequacy Ratio) has a positive effect to stock price is declined. KAP (Earning Assets) has a negative effect and no significant to stock prices. Therefore, the second hypothesis (H2) which states that the KAP (Earning Assets) has a positive effect to stock price is declined. BOPO (Operating Expenses to Operating Income) has a negative effect and significant to stock price. Therefor, the third hypothesis (H3) which states that BOPO (Operating Expenses to Operating Income) has a negative effect to stock price is received. LDR (Loan to Deposit Ratio) has a negative effect and no significant to stock price. Therefore, the fourth hypothesis (H4) which states that the LDR (Loan to Deposit ratio) has a positive effect to stock prices is declined.Keywords: CAR, KAP, BOPO, LDR, stock price